Interfaith Communication on Social Media: Content Analysis Log In, Eps 30 “Tolerance, We Make History” - Hidayah, Childa Tanzilul (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2024)
This study examines the representation of interfaith communication in social media content through an analysis of the Log In program episode 30 entitled "Tolerance, We Print History". As one of the contents that discusses the issue of religious tolerance on digital platforms, this episode is an important object of study to understand how dialogue and interaction between religious communities are constructed and conveyed through social media. Using a qualitative content analysis method, this study aims to identify communication patterns, narratives, and tolerance values built in the episode. The analysis was carried out by paying attention to three main aspects: (1) the way to convey the message of interfaith tolerance, (2) the representation of interfaith dialogue, and (3) the framing strategy of sensitive issues related to religion. The results of the study show that Log In episode 30 succeeded in building a narrative of tolerance through a storytelling approach that presents real stories about harmony between religious communities. This program is also effective in presenting constructive dialogue involving perspectives from various religions, while maintaining the sensitivity of religious issues. Other important findings are the use of inclusive language and visuals, as well as messaging strategies that prioritize universal human values. This research contributes to the understanding of how social media content can play a role in building positive interfaith communication and supporting the creation of religious tolerance in the digital era. Keywords: interfaith communication, content analysis, Log In, religious tolerance, social media, interfaith dialogue   Abstrak Penelitian ini mengkaji representasi komunikasi antar agama dalam konten media sosial melalui analisis terhadap program Log In episode 30 yang bertajuk “Toleransi, Kita Cetak Sejarah”. Sebagai salah satu konten yang membahas isu toleransi beragama di platform digital, episode ini menjadi objek kajian penting untuk memahami bagaimana dialog dan interaksi antarumat beragama dikonstruksi dan disampaikan melalui media sosial. Menggunakan metode analisis konten kualitatif, penelitian ini bertujuan untuk mengidentifikasi pola-pola komunikasi, narasi, dan nilai-nilai toleransi yang dibangun dalam episode tersebut. Analisis dilakukan dengan memperhatikan tiga aspek utama: (1) cara penyampaian pesan toleransi antar agama, (2) representasi dialog antariman, dan (3) strategi pembingkaian isu sensitif terkait keagamaan. Hasil penelitian menunjukkan bahwa Log In episode 30 berhasil membangun narasi toleransi melalui pendekatan storytelling yang menghadirkan kisah-kisah nyata tentang harmoni antarumat beragama. Program ini juga efektif dalam menyajikan dialog konstruktif yang melibatkan perspektif dari berbagai agama, sambil tetap menjaga sensitivitas isu keagamaan. Temuan penting lainnya adalah penggunaan bahasa dan visual yang inklusif, serta strategi penyampaian pesan yang mengutamakan nilai-nilai kemanusiaan universal. Penelitian ini memberikan kontribusi pada pemahaman tentang bagaimana konten media sosial dapat berperan dalam membangun komunikasi antar agama yang positif dan mendukung terciptanya toleransi beragama di era digital. Kata Kunci: komunikasi antar agama, analisis konten, Log In, toleransi beragama, media sosial, dialog antariman